Strategi Dakwah Terhadap Non-Muslim: Studi atas Pandangan Nawāwī Al-Jawīdalam Tafsīr Marāḥ Labīd - Ghozali, Mahbub; Aula, Siti Khodijah Nurul (el Buhuth: Borneo Journal of Islamic Studies, 2023)
This study aims to determine strategy of da'wah to non-Muslims contained in Tafsīr Marāḥ Labīd by Nawawī al-Jāwī. Da'wah activities carried out against non-Muslims are always aimed at inviting them to convert Islam. This is contrary to the messages contained in the Qur'an and the values of religious freedom guaranteed by the state. This study uses a qualitative method with data analysis using content analysis. This study concludes that da'wah to non-Muslims in Nawawi's view is not in the form of an effort to invite them to Islam, but the delivery of a message to well behaved. The issue of faith, in Nawawi's view, is a guide that can only be given by God. In order for the message of da'wah to be conveyed, Nawawi emphasizes the da'wah method used that is not violent. This prohibition is absolute, except in the process the preacher experiences threats that can interfere with faith. However, Nawawī emphasized that if this happens and it is possible to avoid it, then a preacher is advised to avoid and not to resort to violence. In this context, Nawawī also prohibits acts of da'wah in the name of jihad in the form of violence.